PENINGKATAN PEMBELAJARAN MENULIS PUISI BERBASIS TERJEMAHAN AL-QURAN MELALUI KOMPONEN PEMODELAN SISWA KELAS X-1 MAN 1 PADANGSIDIMPUAN - Mahli .; Hasanuddin WS; Atmazaki . (Fakultas Bahasa dan Seni UNP, 2013)
Abstract :This research conducted based on the students’ inability to express ideas in poetry Writing. This could be seen from the average score of their learning achievenment which was under the Minimum Standard of Achievement (KKM). This was a classroom action research which was conducted in order to explain the process of improving Al-Qur’an translation based learning in poetry writing through modeling approach in class X-1 of MAN 1 Padangsidimpuan. There were 28 students involved as the subject of this research. The data was collected by using qualitative approach and supported by the quantitative one. In collecting the data, the researcher used observation sheet, field note and interview. This research was conducted in two cycles and four meetings. In conducting this research, the research collaborated with one of the Indonesia Language teachers. The research findings showed that the use of modeling approach could improve the students’ ability in poetry writing. In the first cycle, their average score in poetry writing was 61,34 and then it became 73,82 in the third cycle. The improvement involved all of indicators in poetry writing. Based on the research finding, it can be concluded that (1) the application of Al-Qur’an translation-based learning process can improve the student’s learning achievement in poerty writing in class X-1 of MAN 1 Padangsidimpuan, (2) there are some factors that affect learning process, some of them are (a) teachers’ strategy in adapting the method and the learning materials, (b) the changing of students’ behavior in poetry writing in which there is an interaction between the students and the teachers in learning process.